TOTAL in Kazakhstan: 20 years of partnership - Brendan, McMahon (KSU publ., 2015)
It is noted that the TOTAL company, being one of world leaders in nevtegazovy sector, plays an important role in North Kaspiysk the project. It is emphasized that the important step for development of business in Kazakhstan was taken when TOTAL got shares in two prospecting blocks in the south of the Aktyubinsk area. It is specified that the company continues to strengthen strategic partnership with the KazMunaiGas National company, actively developing joint prospecting projects. The conclusion is drawn that one of the main priorities of corporate policy of TOTAL concern is ensuring industrial and ecological safety at all stages of work. It is described how TOTAL actively participates in adjustment of the close business and cultural relations between Kazakhstan and France, being one of the leading international corporations and the largest French company.
Қазақстандағы TOTAL: əріптестікке 20 жыл
TOTAL в Казахстане: 20 лет партнерства
Keywords: market of energy resources; relationship; strategic investor; business; corporate policy; oil and gas projects; cooperation; forum